PENGEMBANGAN ALAT IMITASI RANTAI UNTUK TEKNIK PUTARAN PADA CABANG OLAHRAGA ATLETIK LONTAR MARTIL - Rahmad Rizky; Widyan pratama (Journal Physical Health Recreation (JPHR), 2021)
This study aims to develop a rotary technique tool in the athletic sport of hammer throwing. Hammerhead throwing has an average of 81.00%, it can be concluded that it takes a tool that can train the rotation technique in the hammer-throwing athletic sport in the Hammerhead Throwing sport which includes the rotation in the throwing process. At the validation stage, the expert design assessed by 6 experts namely Sports Expert, Coach, and Media Expert had an average score of 79.00%. In the period after design validation there was a pandemic that hit the world caused by a virus with the name Covid-19, the whole world went into lockdown or quarantine including the Lontar Hammer athlete community, therefore the trials carried out in each club were abolished but the testing method was replaced by increasing the number experts who assess the feasibility of the tool to be used in the training process. The product trial stage was carried out by an athlete at the provincial level who represented North Sumatra at the 2016 PON event in West Java on this training tool and then assessed by 6 experts, namely 2 Sports Experts, 2 Coaches, and 2 Media Experts, the average value of the validity of the six being 82.00 %. Then made improvements according to input from experts. After that, the use trial phase was carried out using the same method and number of experts with the average value of the validity of the six being 90.00%. The conclusion that resulted from the trial use or the last stage of this research was the creation of a chain imitation exercise tool for the round technique of the athletic sport of hammer throwing numbers that was sophisticated and flexible for all user groups to help train rotation techniques in athletic sports, especially in the rotating movement of the hammer throwing tool. . From the results of the assessment of 2 sports experts (academics), 2 material experts (coaches) and 2 media experts, the tool is categorized as good/worthy to be used as an exercise tool in sports. In the conditions of the Covid-19 pandemic, the device was not tested on athletes widely to prevent transmission, but was only tested by an athlete at the national level, after which the performance of the device would be assessed by an expert.